Trehalose‐6‐Phosphate Phosphatase SlTPP1 Adjusts Diurnal Carbohydrate Partitioning in Tomato - Chai, Lin; Wang, Heng; Yu, Hongjun; Li, Hongxue; Yi, Debao; Ikram, Sufian; Cao, YiDan; Zhao, Caili; Lu, Tao; Li, Yang; Jiang, Weijie; Li, Qiang (Plant, cell and environment, 2025)
ABSTRACT Trehalose 6‐phosphate phosphatases (TPPs) play essential roles in carbohydrate distribution between source and sink organs in plants. Here, we show that TPPs also participate in regulating diurnal carbohydrate partitioning. In tomato, SlTPP1 exhibited high expression in leaves, particularly in phloem, with distinct diurnal variation. Overexpression of SlTPP1 promoted plant growth and biomass accumulation, whereas its knockout reduced both. Analysis of photosynthesis parameters revealed that overexpression of SlTPP1 accelerated the initiation of photosynthesis at dawn, promoting assimilate production. Additionally, SlTPP1 enhanced the stem's buffering capacity in diurnal carbohydrate partitioning, promoting daytime carbohydrate accumulation and facilitating nocturnal carbohydrate export to the roots, resulting in increased root carbohydrate levels. These results indicate that SlTPP1 regulates diurnal carbohydrate partitioning, establishing a positive feedback loop that promotes plant growth. Notably, overexpression of SlTPP1 reduced T6P concentration, whereas overexpression of SnRK1 (sucrose non‐fermenting 1‐related protein kinase) α subunit (SNF1) decreased biomass and did not enhance the stem's buffering capacity in carbohydrate partitioning. These findings suggest that SlTPP1's regulation of diurnal carbohydrate partitioning is at least partially independent of the classical T6P‐SnRK1 pathway. Summary statement In tomato, SlTPP1 enhances the stem's buffering capacity in diurnal carbohydrate partitioning, increases carbohydrate availability in the leaves and accelerates the initiation of photosynthesis at dawn, thus establishing a positive feedback loop that promotes plant growth.